1995
DOI: 10.1007/bf02254770
|View full text |Cite
|
Sign up to set email alerts
|

Mevalonate regulates polysome distribution and blocks translation-dependent suppression of 3-hydroxy-3-methylglutaryl coenzyme A reductase mRNA: Relationship to translational control

Abstract: We reported previously that 3-hydroxy-3-methylglutaryl coenzyme A reductase synthesis is regulated at the translational level by mevalonate. To determine at what stage mevalonate affects reductase synthesis, we examined the distribution of reductase mRNA in polysomes from cells treated with lovastatin alone; lovastatin and 25-hydroxycholesterol; or lovastatin, 25-hydroxycholesterol, and mevalonate. In lovastatin-treated cells, reductase mRNA was primarily associated with heavy polysome fractions. When 25-hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…The results show the three splice variants, CB, CB(Ϫ2), and CB(Ϫ2,3), to be similarly distributed in the sucrose gradient. Thus, 60 -75% of each message was present in fractions 5-12, which contain polysomes (32). Similar proportions of the abundant constitutive mRNA for glyceraldehyde-3-phosphate dehydrogenase were found in these same fractions.…”
Section: Transcripts Missing Exons 2 and 3 From A375 Human Melanoma Cmentioning
confidence: 69%
See 2 more Smart Citations
“…The results show the three splice variants, CB, CB(Ϫ2), and CB(Ϫ2,3), to be similarly distributed in the sucrose gradient. Thus, 60 -75% of each message was present in fractions 5-12, which contain polysomes (32). Similar proportions of the abundant constitutive mRNA for glyceraldehyde-3-phosphate dehydrogenase were found in these same fractions.…”
Section: Transcripts Missing Exons 2 and 3 From A375 Human Melanoma Cmentioning
confidence: 69%
“…2 and under "Experimental Procedures." Fraction 5 corresponds to the position of the 80 S ribosome peak (32). Shown are the amounts RNA or PCR product recovered in the indicated fractions as a percent of the total.…”
Section: Table I Distribution Of Variant Cathepsin B Mrnas In Polysommentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the uncoupling of HMG CoA reductase activity from sterol-mediated feedback regulation was shown to occur in diverse tumors as well as in embryonic and differentiating tissues and in carcinogen-treated and regenerating liver (107)(108)(109)(110)(111)(112)(113)(114)(115). George and Goldfarb (108) reported that the elevated sterol feedback-resistant HMG CoA reductase activity in tumors retains sensitivity to feedback regulation by mevalonate; as delineated above, farnesol appears to be the mevalonate-derived nonsterol feedback mediator of both the translation of HMG CoA reductase mRNA (59,101) and HMG CoA reductase degradation (81,82). A second study detailing the anomalies in tumor HMG CoA reductase activity is depicted in a report by Bennis et al (115).…”
mentioning
confidence: 99%
“…The discrepancy between large changes in enzyme activity and rates of synthesis, independent of a change in HMG CoA reductase mRNA level, points to a translational control mechanism, one that is mediated by a nonsterol mevalonate-derived product of the mevalonate pathway. We found that a mevalonate-derived nonsterol product distal to farnesyl diphosphate and proximal to lanosterol in the sterol pathway (59) suppresses HMG CoA reductase synthesis by reducing the efficiency of HMG CoA reductase mRNA translation (59,101). Candidate regulatory signal molecules include squalene, farnesyl pyrophosphate or a derivative (farnesol), or farnesyl-pyrophosphate-generated inorganic pyrophosphate (102).…”
mentioning
confidence: 99%